ANALISIS SNAKE LINE UNTUK SISTEM PERINGATAN ALIRAN LAHAR DINGIN (STUDI KASUS KALI PUTIH, GUNUNG MERAPI) - , Nina Yulinsa ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Lahar flow in region of Mount Merapi after an eruption of 2010 is still considered potentially to happem and threat to the region around the river from the upstream of Mount Merapi. The development of warning criteria against the potential occurance of lahar flow is a thing that should be done continuoslu, with regards to the dynamics data availability (rainfall data and lahar flow occurance data), although with limited data. This study aims to find out of warning system including snake line as a rain phenomenon in putihâs catchtment area which will affect on the occurance of lahar flow, evaluate the success rate of snake line for deciding the warning system. As a main reference to be used is Guidelines for Development of Warning and Evacuation System Against Sediment Disasters in Developing Countries yang diterbitkan oleh Ministry of Land, Infrastructure and Transport Infrastructure Development Institute â Japan. This research was conducted through several stages: preparation, secondary data collection in the form of rainfall data, lahar flow occurance data, analysis of rainfall which lead and does not lead into lahar flow, the making of graph relations between rainfall intensity with working rainfall, determination of critical line, warning line and evacuation line, depiction of snake line as well as evaluation of snake line toward warning criteria being produced. The results showed that the rainfall standard in Putih River: for warning is 18 mm and for evacuation is 45 mm. The accuracy of warning criteria and evacuation againts snake line for warning line is 30%, evacuation line is 61% and critical line is 83%. The behavior of snake line that cause lahar flow in Putih River, forming an angle 40o till 45o.